Juridical Analysis of Prosecutor's Error in Adding Articles to the Indictment - Joko Susanto; Falikha Ardiyani Zjubaidi; Ignatius Henri Pelupessy; Mudassar Ali Mughal (IJCLS (Indonesian Journal of Criminal Law Studies), 2025)
This research investigates the procedural legality and judicial consequences of the Public Prosecutor's (JPU) error in adding paragraph norms to the indictment, with a focus on Decision No. 8/Pid.B/2025/PN Smg. In the Indonesian criminal justice system, the indictment serves as the legal basis for the court’s decision. Errors in drafting the indictment can violate the rights of the accused and undermine the integrity of the legal system. In this case, the original charges referred to Articles 263(1), 264(1), and 266(1) of the Criminal Code. However, in the second indictment, the prosecutor added a paragraph stating that the defendant committed forgery of an authentic deed under Article 264(1), although this provision was not included in the original indictment. This study focuses on normative juridical research, also known as library or document study, which relies primarily on secondary data available in libraries. The study adopts a qualitative approach. The research found that the prosecutor's error was caused by a lack of understanding of legal provisions, external pressures, and tight deadlines in preparing the indictment. The addition of the paragraph created legal uncertainty, which could potentially erode public confidence in the justice system. Based on these findings, this research recommends continuous legal training for prosecutors, strengthening oversight mechanisms in the prosecution process, and imposing sanctions for negligence to improve the quality of prosecution, protect defendants' rights, and maintain the integrity of Indonesia's criminal justice system.